Annulment of Marriage Due to Identity Forgery in the Perspective of Islamic Law - Apriyani, Eka Putri; Muchtar, M Ilham; Rapung, Rapung (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2024)
Marriage is an inner birth bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the One True Godhead. Marriage must be carried out in accordance with the Shari'a and comply with its conditions and harmony. And if it does not meet the conditions and get along well, then the marriage will be void. The formulation of the problem in this study is how the picture of identity forgery in marriage and how the Islamic legal perspective related to marriage annulment due to identity forgery. This research is classified as Library Research research with a qualitative approach, meaning that this research does not go directly into the field in finding data sources. Library research is used to obtain written data relating to the object of research with the intention of being able to analyze identity forgery. The data sources used by researchers are primary data and secondary data then analyzed to obtain conclusions and aim to reveal describing the data obtained. The results of this study are, first: Based on the Law on Marriage No.1 of 1974 Article 2 paragraph 1 where